PERANCANGAN DAN PENERAPAN APLIKASI TECHNOPRENEURSHIP DENGAN MENERAPKAN E-COMMERCE PADA UMKM GUNA MENINGKATKAN DAYA SAING (STUDI KASUS PADA UMKM TOKO DEDE GORDYN) - Utari, Tituk (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
Micro, Small and Medium Enterprises (MSMEs) are one of the factors that influence economic growth in Indonesia. Problems often faced by MSMEs are difficulties in marketing products. Toko Dede Gordyn located in Yogyakarta is a UMKM that sells various types of curtains and accessories. Data management systems, both product data and sales data and marketing activities are still carried out in the conventional way. This marketing system also has a big disadvantage, that is marketing is only local or around the area. This study aims to design and implement e-commerce technology in improving production marketing strategies. E-commerce technology is built using website-based applications. This application uses prestashop CMS tools so that businesses can promote business results easily. This study uses a prototype test with the aim to find out whether the prototype made has met the needs of users. The results of this test describe the advantages of a new system compared to the old system. The conclusion of the results of this study is that the existence of e-commerce applications can introduce existing products in the Dede Gordyn Store so that it can increase the number of sales.